OAUNI astronomical photometry: Stellar variability of FO Aqr on 2016 low state - Pereyra A. (2020)
This work reports a photometric monitoring of the intermediate polar cataclysmic variable star FO Aqr. This is part of the ongoing OAUNI stellar variability program. Around 1200 individual measurements (or ? 9 hrs of observations) were gathered distributed in five nights. The observation epoch was coincident with the 2016 low state brightness of FO Aqr. Good quality light curves detect unambiguously the expected stellar variability of FO Aqr. The analysis using periodograms let to determine the main two known periods, P1 = 20.380 ± .003 min and P2 = 11.076 ± .001 min. Our full five-nights analysis shows that P1, the spin white dwarf period, is more prominent than P2, the one-half of the beat period between the spin and orbital periods. Nevertheless, individual light curves show than, at least in one case, a reverse pattern is found. It suggests a dependence of the beat period with the orbital phase of the system with important variations at the same phase interval.